HALLAZGO DE LAURELIOPSIS PHILIPPIANA (LOOSER) SCHODDE (ATHEROSPERMATACEAE) EN EL AREA COSTERA DE LA REGION DEL MAULE, CHILE CENTRAL - Sepúlveda, César A.; Troncoso A., Alejandro (Gayana Botánica, 2004)
We report the finding of Laureliopsis philippiana (Looser) Schodde (Atherospermataceae) in the coastal area of the Maule Region (35°29’ S and 72°22’W) in central Chile. The new locality (San Pedro - Las Cañas) extends by some 240 km the northern limit of the species, which is associated mainly with the temperate rainforests further south.